EFOD : the epigenetic factors online database. - Li, Hui. (2009)
The Epigenetic Factors Online Database (EFOD) is an open source database accessible on the World Wide Web through the URL: http://vhp.ntu.edu.sg/efod. Taking the convenience and cost-effectiveness of the internet, the details of epigenetic factors can be made more accessible to its target students, researchers, as well as the general public. It was designed to promote the exchange of information as well as the assembly of genes participated in various epigenetic mechanisms. The database of EFOD was constructed using freely available software including Apache HTTP Server 2.2.6, MySQL 5.0.45, PHP 5.2.8, and PHPmyadmin 2.11.4-rc1. The major source of the dataset was the publication titled “New Nomenclature for Chromatin Modifying Enzymes” by C. David Allis et al., as published in Cell 131, 2007. A total of 146 genes in EFOD were collected for humans (100), Drosophila melanogaster (19), Saccharomyces cerevisiae (15), and Schizosaccharomyces pombe (12). They can be searched using keywords, enzyme category, gene ID, protein and mRNA accession numbers, as well as their major functions. EFOD also provides a tool for researchers to submit their newly discovered genes into the database. With these functions equipped, EFOD aims to facilitate the future studies and understandings in epigenetics.